Kinematics Control of 3-DOF Under-constrained Parallel Robot with Variable Cable Mast Angles - Zhao Tao; Ding Xiaojun; Zhao Hu; Zheng Yi; Ma Jianrui (Jixie chuandong)
The cable-driven parallel robot is a special type of parallel robots whose end-effector is driven by cables instead of rigid rods. A three-degree-of-freedom (3-DOF) under-constrained parallel robot with variable cable mast angle is studied. The inverse kinematics model of the robot is established by using the vector closed-loop principle. According to the Lagrange equation, the dynamics model of the robot is established. Based on the robot PD control theory of model compensation, a PD controller of the robot is designed. Given a motion trajectory of the end-effector of the robot, the pose change of the end-effector is transformed into cable length change through the inverse kinematics of the robot. The cable length is used as the input of the control system. The experimental results verify the correctness of the inverse kinematics and dynamics model of the robot and the effectiveness of the control method.